With the benefit of hindsight : valedictory reflections from departmental secretaries, 2004-11 - Wanna, John; Vincent, Sam; Podger, A. S. (Andrew S.) (ANZSOG (Series), 2012)
"This collection brings together the valedictory speeches and essays from a departing group of secretaries (and one or two other equivalent agency heads) who left the Australian Public Service between 2004 and 2011"--Abstract